Operational report for the Fourth Caribbean Week of Agriculture - Browman, John S. L. (IICA GeorgetownGY, 2004)
Reports on various aspects of the week of agriculture viz. the setting, context and events; the organization; preparation operations; promotion of the CWA 2003; selected highlights of the events of the CWA 2003; media coverage; and, finance and general accounting.